Incidence of intradialytic complications and their risk factors in patients undergoing hemodialysis in hospitals affiliated to Medical University of Hamadan Iran - Ghahri Sarabi, Alireza; Torabi, Mohammad; Abed Saeedi, Zhila; Akbarzadeh Baghban, Alireza (Advances in Nursing & Midwifery, 2012)
Incidence of intradialytic complications and their risk factors in patients undergoing hemodialysis in hospitals affiliated to Medical University of Hamadan Iran Ghahri Sarabi, AR.1 (MSN); Torabi, M.2 (MSN); Abed Saeedi, Zh.3 (PhD); Akbarzadeh Baghban, A.4 (PhD) 1. Lecture, Dept. of Medical Surgical, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran. Iran. 2. Alumnus, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences. Tehran. Iran 3. Assistant Professor, Dept. of Medical Surgical, Faculty of Nursing & Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. 4. Assistant Professor, Dept. of Biostatistics. Faculty of Paramedical, Shahid Beheshti University of Medical Sciences, Tehran, Iran. Abstract Background and aim Hemodialysis is one the most common renal replacement therapies in end stage renal disease. Despite progress in dialysis technology, intradialytic complications occur frequently. The aim of this study was to determine the rate of intradialytic complications and their risk factors in patients undergoing hemodialysis in hospitals affiliated to Medical University of Hamedan Iran in 2009. Materials and methods 192 patients undergoing hemodialysis participated in this descriptive correlational study. These patients were included in the study using census method. Data were collected by1- a questionnaire which consisted of 3 sections (demographic information, person – related factors and therapy- related factors),2-a check list and clinical examination ( blood pressure and weight measurement). Content validity of the questionnaire was assessed by 10 nursing experts, 5 staff of hemodialysis wards and 2 nephrologists. Reliability of check list was measured using inter-rater reliability (r=0.98). Data were collected by the second author. Data were analyzed by SPSS 15. Findings Findings showed that the most frequent complications include: hypotension (%15.1), muscle cramp(%11.5), nausea(%9.4), headache(%7.8), angina(%2.6), vomiting (%2.1) and itching(%1.6) respectively. Logistic regression analysis, showed a significant correlation between age and cramp (person – related causes) and a significant correlation between hypotension, cramp with vomiting and headache. Moreover, findings showed a significant correlation between nausea with eating during dialysis (patient- related causes); and between hypotension with dialysis solution (therapy- related causes). Conclusion Based on the results of this study, most of intradialytic complications can be prevented. Use of these findings can improve the process of dialysis. Keywords: Hemodialysis, Intradialytic hemodialysis complications *Corresponding Author: Alireza Ghahri Sarabi, department of Medical-Surgical nursing, school of nursing and midwifery, Shahid beheshti University of Medical Sciences and Health Services, Tehran, Iran. E-mail: ARGS1340@yahoo.com